Heart transplantation in a patient with heteroresistant vancomycin‐intermediate Staphylococcus aureus ventricular assist device mediastinitis and bacteremia. Issue 5 (1st August 2013) - Swartz, T.H.; Huprikar, S.; LaBombardi, V.; Pinney, S.; Anyanwu, A.; Lee, M.; Patel, G.
Abstract: Vancomycin‐intermediate Staphylococcus aureus (VISA) infections are an emerging problem and antibiotic options are limited. We report the first case, to our knowledge, of heteroresistant VISA mediastinitis and bacteremia in a patient with a ventricular assist device who underwent orthotopic heart transplantation with clinical cure.